Hyperpiliation, not loss of pilus retraction, reduces Pseudomonas aeruginosa pathogenicity - Sara L. N. Kilmury; Katherine J. Graham; Ryan P. Lamers; Lesley T. MacNeil; Lori L. Burrows (Microbiology Spectrum)
ABSTRACT Type IVa pili (T4aP) are important virulence factors for many bacterial pathogens. Previous studies suggested that the retraction ATPase, PilT, modulates pathogenicity due to its critical role in pilus dynamics and twitching motility. Here we use a Caenorhabditis elegans slow-killing model to show that hyperpiliation, not loss of pilus retraction, reduces virulence of Pseudomonas aeruginosa strains PAK and PA14. Hyperactivating point mutations in the P. aeruginosa PilSR two-component system that controls transcription of the major pilin gene, pilA, increased levels of surface pili to the same extent as deleting pilT, without impairing twitching motility. These functionally hyperpiliated PilSR mutants had significant defects in pathogenicity that were rescued by deleting pilA or through disruption of hyperpiliation via deletion of the type III secretion system needle-length regulator, PscP. Hyperpiliated pilT deletion or pilO point mutants showed similar PilA-dependent impairments in virulence, validating the phenotype. Together, our data support a model where a surfeit of pili reduces virulence, potentially through the prevention of effective engagement of contact-dependent virulence factors. These findings suggest that the role of T4aP retraction in virulence should be revised.IMPORTANCEPseudomonas aeruginosa is a major contributor to hospital-acquired infections and particularly problematic due to its intrinsic resistance to many front-line antibiotics. Strategies to combat this and other important pathogens include the development of anti-virulence therapeutics. We show that the pathogenicity of P. aeruginosa is impaired when the amount of T4aP expressed on the cell surface increases, independent of the bacteria’s ability to twitch. We propose that having excess T4aP on the cell surface may physically interfere with productive engagement of the contact-dependent type III secretion toxin delivery system. A better understanding of how T4aP modulate interaction of bacteria with target cells will improve the design of therapeutics targeting components involved in the regulation of T4aP expression and function to reduce the clinical burden of P. aeruginosa and other T4aP-expressing bacteria.